Mammalian LIN-7 PDZ proteins associate with β-catenin at the cell–cell junctions of epithelia and neurons - Perego, C. (Oxford University Press, 2000)
The heterotrimeric PDZ complex containing LIN-2, LIN-7 and LIN-10 is known to be involved in the organization of epithelial and neuronal junctions in Caenorhabditis elegans and mammals. We report here that mammalian LIN-7 PDZ proteins form a complex with cadherin and β-catenin in epithelia and neurons. The association of LIN-7 with cadherin and β-catenin is Ca(2+) dependent and is mediated by the direct binding of LIN-7 to the C-terminal PDZ target sequence of β-catenin, as demonstrated by means of co-immunoprecipitation experiments and in vitro binding assays with the recombinant glutathione S-transferase:LIN-7A. The presence of β-catenin at the junction is required in order to relocate LIN-7 from the cytosol to cadherin-mediated adhesions, thus indicating that LIN-7 junctional recruitment is β-catenin dependent and that one functional role of the binding is to localize LIN-7. Moreover, when LIN-7 is present at the β-catenin-containing junctions, it determines the accumulation of binding partners, thus suggesting the mechanism by which β-catenin mediates the organization of the junctional domain.